Memorandum of Understanding between the University of Court of the University of Aberdeen and BRAC University (2009) - The University Court, University of Aberdeen; James P. Grant School of Public Health, BRAC University (University of Aberdeen and BRAC University, 2013)
Memorandum of Understanding between the University Court of the University of Aberdeen, a charity registered in Scotland under number SCO13683, and having registered address at University office, King’s College, Regent walk, Aberdeen, AB24 3FX, United Kingdom, acting through Ipact, Health Sciences Building, Foresterhill, Aberdeen AB25 2ZD, United Kingdom (hereinafter “Ipact”), and James P Grant School of Public Health, BRAC University, Civil Engineers Building, 5th Floor, 66 Mohakhali, Dhaka 1212, Bangladesh (hereinafter “JPGSPH”)